2019
DOI: 10.1177/1750458919868903
|View full text |Cite
|
Sign up to set email alerts
|

Influence of early postoperative showering in undressed surgical wound for better clinical outcome

Abstract: Surgeons instruct the patients to avoid postoperative bathing and dress the wounds until the sutures are removed. All wounds were sutured at the end of surgery and kept undressed. Participants received a tap water body bath where the water covered the wound after 24h of surgery. The control group were asked not to wet the dressed surgical site until wound inspection on days 3 and 5. The patients were followed up in the surgery clinic on days 14 and 30 after surgery, when age, sex and type of surgery-matched co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Across all procedures the rate of surgical site infection was lower in the group that was allowed to bathe after 24 hours. 14 These findings further support the idea that rather than increase the risk of infection, allowing patients to bathe soon after surgery may actually decrease the risk of surgical site infection.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Across all procedures the rate of surgical site infection was lower in the group that was allowed to bathe after 24 hours. 14 These findings further support the idea that rather than increase the risk of infection, allowing patients to bathe soon after surgery may actually decrease the risk of surgical site infection.…”
Section: Discussionsupporting
confidence: 60%
“…In fact, the few studies that compare longer versus shorter lengths of restriction have found either no differences in the rate of surgical site infection or decreased surgical site infections when patients were allowed to bathe sooner. 7,13,14 Early cellular changes at the wound bed may provide sufficient protection against infection within 24 hours to allow for bathing. 15 In a systematic review conducted by Harrison et al the authors included 4 papers published between 1946 and 2016.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that to optimize the outcomes, surgical wounds should be kept moist, clean and patients should be advised early moblisation. 11 Another recent study favored early showering in patients after coronary artery bypass graft surgery. This study had the evidence that the rate of sternal wound infections was lower is shower group as compared to non-shower group i.e.…”
Section: Discussionmentioning
confidence: 99%